Investigation of tyre pressure drop phenomenon using specially designed real-time data mining and storage system - Subramonian, Sivarao; Jayahkundy, Raguvaran; Ali, Aidy; Abdullah, Mohamad Faizal; Dhar Malingam, Sivakumar; Md Ali, Mohd Amran; Arep @ Ariff, Hambali; Salleh, Mohd Shukor; Vates, Umesh Kumar (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Tyre pressure plays an important role in ensuring safe operation and performance of a motor vehicle. Improper monitoring of tyre pressure always results in reduction of gas mileage, tyre life, vehicle safety and performance. Studies reflects that, properly inflated tyres can increase tyre life span up to 20% which is equivalent to nine months of its life span, save fuel from 4% to 10%, increase braking efficiency up to 20%, lightens steering system and ease self-steer. Monitoring proper tyre pressure using manual gauges are less effective as they tend to provide slight gap at the valve for air leakage during pressure checking. Therefore, a device called tyre pressure monitoring system (TPMS) is used in the current research to efficiently monitor air pressure and temperature in the tyre of a motor vehicle which then generates a signal indicative of the pressure and temperature in each of the tyre thus increasing the monitoring system of a vehicle and its safety. This paper presents a “cost-effective” real-time data plotting application based on LabVIEW graphical user interface using a TPMS device. Notably, the entire system is tailored to the situation whereby with the existence of this interface; tyre researches and scientist would able to effectively monitor and simultaneously plot the tyre pressure and temperature data even at dynamic condition.